Inovasi Penggunaan Drum Bekas untuk Pembakaran Sampah Minim Asap di Desa Damarguna - Hilmy Awalu Faizien; Yoan Ardiansyah; Tigo Suryo Bimantoro; Rehan Anggara; Muhamad Ramdhansyah; Shiva Andjani; Natasya; Fathiya Sarabila; Fayza Safira Hasanah; Fitria Ningsih; Nezia Salsabilla; Cyntia Noor Zahara; Dzikri Auliya Talindiaty; Evi Noviyanti; Muhammad Akbar Zaelani; Meyrani Anggita Putri; Mutasya Dzikri Al Saska; Toto Nurdianto (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
The problem of household waste management in Damarguna Village, Ciledug District, requires the right solution. Damarguna Village is divided into three blocks, namely Pon, Wage and Pahing. From the three blocks, there is only one TPS in the Pon block and open burning of waste causes air pollution and other negative impacts. In an effort to overcome this problem, KKN Students of Swadaya Gunung Jati University have tried to handle this problem by utilizing used barrels as a means of burning waste with minimal smoke. The community is introduced to the use of these barrels, which not only reduce smoke pollution, but can also be used as a burning briquette from the remaining corn cobs as an alternative fuel. This program can successfully increase public awareness in managing waste and show the potential for reducing adverse environmental impacts. This innovation opens up opportunities for Damarguna Village as an example of independent and sustainable waste management, and can be applied in other villages.